2018
DOI: 10.1038/s41467-018-05363-6
|View full text |Cite|
|
Sign up to set email alerts
|

Long range electronic phase separation in CaFe3O5

Abstract: Incomplete transformations from ferromagnetic to charge ordered states in manganite perovskites lead to phase-separated microstructures showing colossal magnetoresistances. However, it is unclear whether electronic matter can show spontaneous separation into multiple phases distinct from the high temperature state. Here we show that paramagnetic CaFe3O5 undergoes separation into two phases with different electronic and spin orders below their joint magnetic transition at 302 K. One phase is charge, orbital and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 27 publications
4
58
2
Order By: Relevance
“…Comparison with other mixed valent Fe 2+ /Fe 3+ oxides shows that neither the charge nor orbital orders require long-range spin order, as evidenced by Fe 2 OBO 3 21,22 and LuFe 2 O 4 23 , both of which have charge and orbital ordering transitions at higher temperatures than their magnetic transitions. However, the weak bonding interactions that shorten Fe–Fe distances in the trimerons do require ferromagnetic alignment of the three core S = 5/2 spins, as demonstrated recently in CaFe 3 O 5 where phase-separated trimeron and non-trimeron ground states are observed 24 . Hence, the rapid emergence of structural fluctuations in proportion to magnetisation on cooling below the long-range magnetic ordering temperature confirms that the direct Fe–Fe bonding interactions are the primary driver of the local distortions in magnetite.…”
Section: Resultsmentioning
confidence: 71%
“…Comparison with other mixed valent Fe 2+ /Fe 3+ oxides shows that neither the charge nor orbital orders require long-range spin order, as evidenced by Fe 2 OBO 3 21,22 and LuFe 2 O 4 23 , both of which have charge and orbital ordering transitions at higher temperatures than their magnetic transitions. However, the weak bonding interactions that shorten Fe–Fe distances in the trimerons do require ferromagnetic alignment of the three core S = 5/2 spins, as demonstrated recently in CaFe 3 O 5 where phase-separated trimeron and non-trimeron ground states are observed 24 . Hence, the rapid emergence of structural fluctuations in proportion to magnetisation on cooling below the long-range magnetic ordering temperature confirms that the direct Fe–Fe bonding interactions are the primary driver of the local distortions in magnetite.…”
Section: Resultsmentioning
confidence: 71%
“…Gerardin et al used Mössbauer spectroscopy to characterise antiferromagnetic order below a T N of 282 K 12 , and suggested a Charge Averaged (CA) state pertaining above T N and a CO state below, with localisation of Fe 3+ and Fe 2+ on distinct sites. More recent work by Hong et al confirms the high temperature CA state, but they report a macroscopic phase separation in their sample below the magnetic ordering transition (reported as T M = 302 K) 13 , They used high resolution diffraction data to clearly observe a single phase above this T M which separates into two phases below. Bond valence sums for the Fe sites suggested that the minority phase remains charge averaged (CA) below the magnetic ordering transition, while the majority phase is charge ordered (CO) with the Fe1 site characterised as Fe 3+ and the Fe2 site as Fe 2+ , reflecting the expectation of the work of Gerardin et al 12 .…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, three oxides—Fe 4 O 5 , CaFe 3 O 5 , and MnFe 3 O 5 , crystallizing in similar structures comprising the divalent ions (Fe 2+ , Mn 2+ , Ca 2+ ) in the prisms and nearly identically charged octahedra (Fe 2.67+ on average)—demonstrate different types of charge order. Upon the charge ordering in the least dense CaFe 3 O 5 with d (Fe−Fe) oct =3.021 Å or 3.014 Å, the iron atoms shift by only ≈0.01 Å and form loosely packed iron trimers, suggesting that the formation of these trimers is rather magnetically mediated . MnFe 3 O 5 with d (Fe−Fe) oct =2.914 Å lies near the crossover point and exhibits a conventional Fe 2+ /Fe 3+ charge separation .…”
Section: Figurementioning
confidence: 99%